Heteroatom coordination induces electric field polarization of single Pt sites to promote hydrogen evolution activity. Issue 15 (1st April 2021) - Peng, Xianyun; Bao, Haihong; Sun, Jiaqiang; Mao, Zhiyong; Qiu, Yuan; Mo, Zhaojun; Zhuo, Longchao; Zhang, Shusheng; Luo, Jun; Liu, Xijun
Abstract : Single Pt atomic sites are stabilized on MXene support via the formation of Pt–O and Pt–Ti bonds. The unique asymmetric coordination environment of single Pt sites induces local electric field polarization, which remarkably enhances HER activity. Abstract : Herein, we reported a kind of single Pt site (Pt-SA) stabilized on an MXene support (Pt-SA/MXene) via the formation of Pt–O and Pt–Ti bonds to effectively catalyze the hydrogen evolution reaction (HER). Due to the local electric field polarization derived from its unique asymmetric coordination, Pt-SA/MXene displays remarkably higher catalytic HER activity in an alkaline electrolyte. In detail, the Pt-SA/MXene electrocatalyst only needs a low overpotential of 33 mV to reach a current density of 10 mA cm −2 and maintains the performance over 27 h. Besides, Pt-SA/MXene also has a competitive mass activity, 23.5 A mgPt −1, at an overpotential of 100 mV, which is 29.4 times greater than that of the commercial Pt/C counterpart. Density functional theory (DFT) calculations revealed that the polarized electric field could efficiently tailor the electronic structure of Pt-SA/MXene and reduce the energy barrier of adsorption/desorption of the H* intermediate step, further improving its HER catalytic activity.